The role of human capital, leadership and organizational culture on organizational performance: examining the effects of learning organization in Malaysian logistics companies / Assoc. Prof. Dr. Sarminah Samad and Prof. Dr. Zaini Abdullah - Samad, Sarminah; Abdullah, Zaini (Malaysia Institute of Transport (MITRANS), 2013)
Internal and external forces have continually reshaping the world's business environment which ultimately influence organizational performance. Lu (2002) suggested that in today's competitive environment, companies and industries need to understand the key factors that influence their survival in business which ultimately help to contribute overall organizational performance. This implies that companies must be able to generate substantial profit by operating at the lowest possible cost. According to Lu (2002) a study conducted in logistics companies indicate that majority of the respondents agreed that logistics management strategy and approaches were among the key factors for companies' performance. These strategies highlight some important aspects that would induce organizational performance. Among the strategies as documented in literature that help in influencing organizational performance are like time based, asset productivity, technology based and relationship based strategies. Meanwhile Lu (2002)) emphasized quality as important factor for the success of companies regardless of sectors…